Flow and heat transfer past a permeable nonlinearly stretching/shrinking sheet in a nanofluid: A revised model with stability analysis - Jahan, S. (Elsevier B.V., 2017)
This article presents a realistic approach for flow and heat transfer over a nonlinearly permeable stretching/shrinking sheet in a nanofluid. Practically, this approach is more acceptable as compared to the previous one where we have to assume the nanoparticle fraction control on boundaries. By doing this, nanoparticle flux is considered zero and nanoparticle fraction adjusts itself accordingly on the boundaries. Now the impact of Buongiorno's model can be applied in a more effective way. With this revised model, we have discussed the impact of numerous parameters on the skin friction coefficient, the local Nusselt number, and the velocity, temperature, and nanoparticle concentration profiles while finding dual solutions. To determine which solution is physically stable and realizable, we performed the stability analysis. Then the flow pattern is observed by drawing streamlines. It is observed that the first solution is stable and thus, physically realizable. The correlation based estimation for the local Nusselt number has also been carried out. The Brownian motion effect becomes negligible for the new revised model. It is found that the local Nusselt number is almost independent of the Brownian motion while the heat transfer rate reduces with the rise in Lewis number and thermophoresis parameter. For the impermeable case, the streamlines are similar to the normal stagnation point flow but the streamlines contract with the increase of suction parameter as the density of streamline increases and is proportional to the fluid velocity. © 2017 Elsevier B.V.